Analisis Kinerja Kontrak Berjangka Komoditi pada Tokyo Grain Exchange – Jepang - Tomy G. Soemapradja (The Winners, 2005)
Futures contract is one of derivative instruments in which its value depends on underlying asset’s price fluctuation in the future. At the beginning, the futures contracts were traded with hedging motive, but now they are traded with speculative motive also. As an agricultural nation, finally, Indonesia has a commodity futures exchange (BBJ) by the end of 2000. Low volume of transactions and less futures alternative on BBJ made Tokyo Grain Exchange (TGE) as the object of this research. The statistical test concluded: The average rate of return of futures portfolio model is greater than average of forex trading of USD, and the risk of futures portfolio model is greater than forex trading of USD.